Enhancing Technopreneurship Project Management System with Coaching and Mentoring Features - Wahyudi, Stephanus Eko; Tileng, Kartika Gianina (Bina Nusantara University, 2017)
This research aimed to find the system features for remote, synchronous, and asynchronous communication and collaboration among the students. The research design was through an exploratory case study. The data collection method was in-depth interview with experienced supervisors and the subject coordinators. The result of the research is the necessary features to be included in the updated version of the information systems. The various coaching and mentoring features can support subject coordinators, supervisors, and students and allow them to complete the subject on time and in accordance with the standards